Legal Politics of Government Instruments in the Development of State Administrative Law - Ahmad Althof 'Athooillah; Alfan Khairul Ichwan (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
This research aims to identify and reconstruct the supervision and control of Government Instruments, especially in the State Administrative Law (HAN) Corridor. The results of the study were obtained by confirming that how do existing legal rules become the basis for state instruments in carrying out their duties and these legal rules regulate the relationship between citizens and the government. The results of this research are that HAN is an instrument used to carry out government tasks, and involves regulations that regulate interactions between the government and citizens. State Administrative Law plays an important role in regulating relations between the government and citizens and in controlling government tasks. This involves legal norms that regulate the duties and authority of state officials or institutions. The use of discretion or the principle of freies ermessen in HAN provides room for administrators to make contextual decisions. However, discretionary limits must be placed to ensure that the policies adopted do not violate social welfare principles.